ANALYSIS OF MANADO CONSUMER PREFERENCE IN BUYING BATIK APPAREL PRODUCT - Sabijono, Graceane (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Apparel industry has become a great opportunity in making profit. Batik apparel product is one of the type products from this industry. Batik apparel products have captured a lot of market share among Manado consumers. It drives many companies to compete in maintaining and attracting new customers. The understanding of consumer preferences in buying batik apparel product could give information for companies to satisfy customers and gain profit. The objectives of this research are: to identify which attribute of batik apparel is the most preferred by consumer and which combination of attributes that gives the highest utilities of ideal consumer preferences of batik apparel products. The population is people who ever buy batik apparel products or who are going to buy batik apparel products with sample 150 respondents using convenience sampling method. The conclusions of this research are as follow: (1) based on importance values analyzing of conjoint analysis, among three attributes of batik apparel products given, price is the most important factor. The second factor is design attribute and followed by store attribute; and (2) the ideal combination of attributes for batik apparel products which has the highest utility in consumer preferences is batik apparel products with hand-writing batik designed, which is offered with lower prices in Specialty store. That ideal combination is mostly preferred by Manado consumers. Keywords: consumer preferences